A Creating a patterned decorative landscape using knitted shear waste on the surface of the paint product - Kamalova, Iroda; Inoyatova, Maftuna; Rustamova , Surayo; Madaliyeva, Mohira (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: The aim is to create a decarative landscape by effectively applying the residual shears of knitted fabric used for garments on the surface of the loaf fabric from woven cotton by gluing the edges with polyester and dice yarn